OPTIMISASI RUTE PENDISTRIBUSIAN SEJENIS PRODUK DENGAN MENGGUNAKAN PROGRAM GOL - Fitri Marlina; Tumpal P. Nababan; M. D. H. Gamal (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
This article discusses a goal programming technique for optimal vehicle routes of distribution of a product. The goal programming used is the weighted one. This technique is implemented in a real life case of distributing a product in a company. Computational experiments show that determination of vehicle routes using goalprogramming technique is more eﬀective than using only driver knowledge, because it is able to satisfy all of goals expected in the distribution process.